Persepsi Kegunaan, Kemudahan, Keamanan dan Kerahasiaan, Serta Kepuasan Wajib Pajak Pengguna E-Filing dan Non E-Filing untuk Pajak Tahunan Orang Pribadi - Ria Adhi Pramesti; Sukirman Sukirman; Icuk Rangga Bawono (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2021)
This study aimed to compare the perceived usefulness, perceived convenience, perceived security and perceived satisfaction of tax payers between users of e-filing and non e-filing. The research located in Tax Office (KPP) Pratama Purwokerto, using primary data and secondary data collected by survey method. The registered taxpayers to use e-filing are 17.831 and the non e-filing are 44.332. Paired t-test was used to compare each variable between users of e-filing and non e-filing. Based on the analysis, it is can be concluded that: (1) there is no difference in perceived usefulness, users of e-filing and non e-filing has the perception that reporting tax return online and manual are equally useful; (2) there is a difference in perceived convenience, the user has a perception that the use of e-filing is more convenience than the manual; (3) there is a difference in perceived security, the user has a perception that the use of e-filing is more secure and confidential than the manual; (4) there is no difference in perceived satisfaction, either the e-filing and non e-filing are equally satisfied; and (5) as a whole, there are differences of perception between users of e-filing and non e-filing, so it can be concluded that the benefits of the usefulness of e-filing is influenced by variables of usability, convenience, security, confidentiality and satisfaction of taxpayers on e-filing.